Detection of an early HIV-1 infection by HIV RNA testing in an Italian blood donor during the preseroconversion window period - Aprili, Giuseppe; Gandini, Giorgio; Piccoli, Pierluigi; Bressan, Fausto; Gironcoli, Marzia De; Mazzi, Romualdo; Parisi, Saverio G.; Gessoni, Gianluca; Marchiori, Giorgio; Franchini, Massimo (Transfusion (Philadelphia, Pa.), 2003)
BACKGROUND: The implementation of NAT technologies for HIV screening has further reduced the diagnostic window in recent HIV infection. There is still a debate regarding the cost effectiveness of genomic screening of blood donations for transfusion‐transmitted viruses (HBV, HCV, HIV). STUDY DESIGN AND METHODS: Since October 2001, at the Transfusion Service of Verona, single‐donation NAT testing for HCV and HIV‐1 (Procleix TMA HIV‐1/HCV Assay) of all blood donations has been performed. CASE REPORT: A case of acute HIV‐1 infection detected by HIV NAT in a repeat blood donor who donated during the preseroconversion window period is reported. All blood components donated were discarded, and the donor started antiretroviral therapy 2 weeks after blood donation. HIV‐1 p24 antigen was still negative 10 days after the HIV‐1 RNA‐positive blood donation. Seroconversion was documented by Day 41 after donation. CONCLUSION: This case report testifies that HIV NAT screening of blood donation is effective in preventing the transmission of HIV infection through blood components.